Oral Text of Genjek in Karangasem Regency - Nyoman Mantra, Ida Bagus; Weda Kusuma, I Nyoman; Suarka, I Nyoman; Rai Putra, Ida Bagus (e-Journal of Linguistics; Vol 11 No 2 (2017): eJL-JulyDO - 10.24843/eJL.2017.v11.i02.p02, 2017)
This study examines the oral text of genjek in Karangasem regency with the main focus was analyzing the structure, function  and meaning of oral text of genjek by using the theory of structure, theory of function and theory of semiotics. The theory of structure was used to analyze the structure of oral text of genjek . The theory of function was used to analyze the function of the oral text of genjek and the theory of semiotics was used to analyze the meaning of the oral text of genjek .The present study was a qualitative study with systematic study that departs from theory to observation on the availability of data for further analysis and data validation. The approach used in this study was a phenomenological approach that moved from the phenomenon of language used in genjek . The implication of this study is expected to provide benefits to the linguistic approach in studying the structure, function and meaning of the other texts and other literary works. In this study, it was found that oral text of genjek is literary work which has macro structure, super structure and micro structure. The function of genjek includes:  entertainment function, education function, function of remembering the past, solidarity function, social control function, social protest and criticism function, and religious function. Meanings of genjek includes: meaning of love, meaning of the collective consciousness, meaning of ritual, existence of social stratification recognition. Creation process of genjek text is done together spontaneously by a group of people who are gathered together. Inheritance process of genjek is done naturally and non-naturally so that genjek can thrive in Karangasem society